Locus of Control Importance Amongst Children with Divorced Families in Different Societies - Mehrad, Aida (International Journal For Research In Educational Studies, 2019)
The family has deep meaning and contribution to children and play a considerable role in their personal and social life. The relation between father and mother can change personality, performance, and attitude of their children toward their life and relationship with others. In this regard, considering the family relationship specifically those who are divorced is super important. The divorce can be the cause of several normal or abnormal behaviors and reactions amongst children in the society (school, work, relative relation). One of these factors is the locus of control that involved children either view own behavior as influencing the events around them (internal) or rather events controlling their fate or destiny (external). Therefore, the current literature review considered on effects of parental divorce on children’s locus of control and examined various investigations and views that have been focused on divorce as a threatening factor which leads to several reactions amongst children.